Experimental and numerical study of forming aluminum stepped tubes by electromagnetic forming method - Javad Esmaeili; Aliakbar Asgharpour; Mohammad Bakhshi-Jooybari; Hamid Gorji; Mohammad Javad Mirnia (Discover Materials)
Abstract Challenges such as limited formability, high springback, and wrinkling in aluminum forming are addressed using electromagnetic forming (EMF), a high-speed technique that accelerates the workpiece for precise forming. This study investigates stepped tube production by EMF, experimentally and using Finite element simulation. A key focus is the detailed exploration of EMF for stepped tubes, resolving issues like uneven thinning and poor material flow. In this study, Aluminum 6063 tubes with a thickness of 0.95 mm were used. A coil was optimized in COMSOL by analyzing parameters such as the number of turns of the coil, wire spacing, and coil-to-workpiece distance to enhance quality. Additionally, implementing air venting channels in the die design eliminated dents and incomplete filling, enhancing production outcomes. Initial single-step tests at 4, 5, and 6 kV showed insufficient filling and excessive thinning, leading to the development of a multi-step approach. In addition, precise three-dimensional modeling with full coupling was improved simulation accuracy for complex geometries. Two-step and four-step methods overcame single-step limitations. Results confirmed that the two-step method at 4 kV and 6.5 kV achieved optimal outcomes, with a 30.67% expansion ratio and a 20% improvement in thickness distribution. An inverse analysis estimated the coefficient C in the Johnson–Cook model, enhancing material behavior predictions. These advancements address EMF challenges and offer opportunities for industries like automotive and aerospace.